The Effect of Counseling Program on Improving Psychological Resilience for First Class Soccer Referees - Thare, Ahmed (Journal of Physical Education, 2021)
Developing referees’ artistic performance inside the field depends on many physical, administrative, psychological, and cognitive aspects. Because of the political and social conditions that sports communities, in general, suffer from and the Iraqi sports community in particular there is a great need to direct more attention to psychological aspects. It became necessary to develop due to the situations that the referee face and solve a matter that will improve their performance. The importance of the research lies in designing a counseling program for improving psychological resilience for soccer referees according to scientific styles that will help them overcome most mistakes and achieve better levels of performance. This the research aim at identifying the effect of counseling program on psychological resilience level in first-class soccer referees.